Phosphorothioate-modified CpG oligodeoxynucleotides mimic autoantigens and reveal a potential role for Toll-like receptor 9 in receptor revision - Marshall, Anne; Ziegler, Saskia; Förmer, Sandra; Rieker, Ralf Joachim; Heeg, Klaus; Bekeredjian-Ding, Isabelle (Immunology, 2013)
Re-expression of recombinase activating genes (RAG) in mature B cells may support autoreactivity by enabling revision of the B-cell receptor (BCR). Recent reports suggest that administration of Toll-like receptor 9 (TLR9) -stimulating CpG oligodeoxynucleotides (ODN) could trigger the manifestation of autoimmune disease and that TLR are involved in the selection processes eliminating autoreactive BCR. The mechanisms involved remain to be elucidated. This prompted us to ask, whether TLR9 could be involved in receptor revision. We found that phosphorothioate-modified CpG ODN (CpGPTO) induced expression of Ku70 and re-expression of RAG-1 in human peripheral blood B lymphocytes and Igλ expression in sorted Igκ+ B cells. Further results revealed unselective binding specificity of CpGPTO-induced immunoglobulin and suggested that CpGPTO engage and/or mimic IgM receptor signalling, an important prerequisite for the initialization of receptor editing or revision. Altogether, our data describe a potential role for TLR9 in receptor revision and suggest that CpGPTO could mimic chromatin-bearing autoantigens by simultaneously engaging the BCR and TLR9 on IgM+ B cells.